Assignment of Immunoglobulin G1 and G2 Concentrations to Pneumococcal Capsular Polysaccharides 3, 6B, 14, 19F, and 23F in Pneumococcal Reference Serum 89-SF - Soininen, Anu (American Society for Microbiology, 1998)
We describe standardization of an enzyme-linked immunosorbent assay (ELISA) for measuring immunoglobulin G1 (IgG1) and IgG2 concentrations of antibodies to pneumococcal capsular polysaccharide (Pnc PS). The ELISA uses a human pneumococcal reference serum pool, lot 89-SF, as a reference. IgG1 and IgG2 concentrations were assigned to antibodies to Pnc PS serotypes 3, 6B, 14, 19F, and 23F in 89-SF by ELISA using affinity-purified monoisotypic IgG1 and IgG2 preparations. The sum of IgG1 and IgG2 concentrations in 89-SF agrees well with the previously assigned IgG concentrations. The IgG1 and IgG2 values in 89-SF were used to measure antibodies to Pnc PS 6B, 14, and 23F in adult pre- and postimmunization sera and the sum of IgG1 and IgG2 concentrations correlated well with the IgG values. Furthermore, the IgG2/IgG1 ratio did not affect the detection of IgG1, the isotype usually represented by a lower concentration.